Epidemiología y parasitismo gastrointestinal en equinos del departamento Maracó, provincia de La Pampa, República Argentina (Veterinary Science, 2017)
An epidemiologic survey of the gastrointestinal parasites that affect equines was carried out in 4 farms in Maracó Department, La Pampa Province, from March 15, 2005 to February 28, 2007.Ten equines chosen randomly from each farm were evaluated. The sample results of faecal matter taken each month showed the h.p.g. porcentages higher in the months of January, February, March, November and December (P 0,001). The species found were Cyatostomun spp. 76%,Triodonthophorus Triodonthophorus spp. 17,5%, Strongylus spp. 4,5 % y Trichostrongylus spp. 2%. Samples of the pastures were taken every fifteen days in the pasture grounds where the equines under study were grazing.The greatest amount of larvae were observed in the months of March,April, May, October and November (P 0,01) and the most important genre found were Cyatostomun spp. 71%, Triodontophorus spp. 19,5%, Strongylus spp. 7,5% yTrichostrongylus spp. 2%.These results suggested that the antiparasitic treatments should be undergone in autumn, spring and summer
Keywords: Equine parasites; Epidemiology; Maracó Department